Reliability of the Thai version of the Spinal Cord Independence Measure Self-Report (SCIM-SR-Thai) - Mekavutikul, Kodchakorn; Tongprasert, Siam (Journal of Associated Medical Sciences, 2025)
Background: The SCIM-SR, a self-report instrument, offers a patient-centered perspective. To ensure its clinical and scientific utility in Thailand, it is essential to establish the reliability of a translated and culturally adapted Thai version. Objectives: To investigate the reliability of the SCIM-SR-Thai in chronic persons with SCI using a test-retest approach after 7 days. Materials and methods: Thai adults aged 20-80 years with chronic SCI for at least 1 year were recruited. Participants filled out the SCIM-SR-Thai in-office once and were given a second copy to be completed at 7 days at their leisure. Participants were instructed to mail the questionnaire back within 14 days or would be considered a drop-out. Results: A total of 59 participants completed the study. The majority were male (62.7%). The mean (SD) age was 48.5 (15.4) with median (IQR) time since SCI of 12 (6-21) years. Most of the participants were diagnosed with T1-S3 AIS A, B, and C 38/59 (64.4%). The SCIM-SR-Thai demonstrated excellent internal consistency and test-retest reliability (Cronbach’s alpha 0.99, ICC=0.97; 95% CI=0.95-0.98). Analyses of individual subscales yielded similar results. Conclusion: SCIM-SR-Thai demonstrates good reliability and internal consistency. The authors encourage adoption of this questionnaire as a standardized tool in clinical practice to assess functional independence in people with SCI.